Papel das casas de cultura estrangeira para a implementação das políticas linguísticas no processo de internacionalização da Universidade Federal do Ceará - Lima, Ruy Ferreira (2021)
Asserting that learning a foreign languages enables interaction with other cultures and other people, it is undeniable the contribution of the Casas de Cultura Estrangeiras to the cultural development of society and to the strengthening of academic engagement. Thus, we believe it is necessary to study the actions aimed at teaching foreign languages developed at UFC, with the objective of examining whether those meet the linguistic policy conceived/implemented in the Institution. This way, and supported by studies on linguistic policy in the context of public policies, we developed this research in order to evaluate the action of university linguistic policy planned/carried out for the teaching of foreign languages in the dynamics of the UFC internationalization process. The general aim is to analyze the role of the Casas de Cultura Estrangeira in the UFC internationalization project, in line with the UFC Internationalization Plan (2017-2021), in the current process of internationalization of higher education. Considering the premise of this research, we opted for the qualitative research method to analyze the perception of teachers and/or managers about the work of the Casas de Cultura Estrangeira in the teaching of foreign languages at the university. It was decided by a study in the context of the UFC, in the scenario of the internationalization process. From the study carried out, it was noticed that the respondents show a lack of knowledge related to internationalization as well as the UFC Internationalization Plan, which did not consider the actions developed by the Casas de Cultura Estrangeira and did not contemplate their vocation for the promotion of the process of internationalization of the UFC, despite its invaluable experience and the great importance to UFC and Ceará society concerning teaching and dissemination of foreign languages and their cultures. In addition, it showed that the UFC Internationalization Plan did not look closely to the potential of the Casas de Cultura Estrangeira to leverage and promote the UFC internationalization process